Poverty of democracy : the institutional roots of political participation in Mexico - Holzner, Claudio A. (Pitt Latin American series., 2010)
"Holzner has crafted a challenging, thoughtful, and provocative interpretation contradicting theories that suggest democracy increases political participation among the poor. This work is particularly relevant to Mexico, but Holzner's conclusions have widespread implications for any society completing the transition to a democratic model. A welcome, fresh insight to the consequences of democratic transitions in the region."--Roderic Ai Camp, Claremont McKenna College.